Alpha-Synuclein Preserves Mitochondrial Fusion and Function in Neuronal Cells. (23rd November 2019) - Faustini, Gaia; Marchesan, Elena; Zonta, Laura; Bono, Federica; Bottani, Emanuela; Longhena, Francesca; Ziviani, Elena; Valerio, Alessandra; Bellucci, Arianna
Abstract : Dysregulations of mitochondria with alterations in trafficking and morphology of these organelles have been related to Parkinson's disease (PD), a neurodegenerative disorder characterized by brain accumulation of Lewy bodies (LB), intraneuronal inclusions mainly composed of α -synuclein ( α -syn) fibrils. Experimental evidence supports that α -syn pathological aggregation can negatively impinge on mitochondrial functions suggesting that this protein may be crucially involved in the control of mitochondrial homeostasis. The aim of this study was to assay this hypothesis by analyzing mitochondrial function and morphology in primary cortical neurons from C57BL/6JOlaHsd α -syn null and C57BL/6J wild-type (wt) mice. Primary cortical neurons from mice lacking α -syn showed decreased respiration capacity measured with a Seahorse XFe24 Extracellular Flux Analyzer. In addition, morphological Airyscan superresolution microscopy showed the presence of fragmented mitochondria while real-time PCR and western blot confirmed altered expression of proteins involved in mitochondrial shape modifications in the primary cortical neurons of α -syn null mice. Transmission electron microscopy (TEM) studies showed that α -syn null neurons exhibited impaired mitochondria-endoplasmic reticulum (ER) physical interaction. Specifically, we identified a decreased number of mitochondria-ER contacts (MERCs) paralleled by a significant increase in ER-mitochondria distance (i.e., MERC length). These findings support that α -syn physiologically preserves mitochondrial functions and homeostasis. Studying α -syn/mitochondria interplay in health and disease is thus pivotal for understanding their involvement in PD and other LB disorders.